Dealing with being the youngest child in your family - Vogel, Elizabeth (New York : PowerKids Press, 2000)
Describes some of the frustrations and benefits that come with being the youngest child in a family and offers advice on how to deal with both.
Includes index.
11 13
Keywords: Youngest child -- Psychology -- Juvenile literature; Sibling rivalry -- Juvenile literature; Birth order -- Psychological aspects -- Juvenile literature; Brothers and sisters; Parenting; Birth order